2015
DOI: 10.1371/journal.pone.0142681
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Seasonal Upwelling on Inorganic and Organic Matter Dynamics in the Water Column of Eastern Pacific Coral Reefs

Abstract: The Gulf of Papagayo at the northern Pacific coast of Costa Rica experiences pronounced seasonal changes in water parameters caused by wind-driven coastal upwelling. While remote sensing and open water sampling already described the physical nature of this upwelling, the spatial and temporal effects on key parameters and processes in the water column have not been investigated yet, although being highly relevant for coral reef functioning. The present study investigated a range of water parameters on two coral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 57 publications
1
34
0
2
Order By: Relevance
“…However, future studies would benefit from collecting samples at a higher spatial or temporal resolution in order to unravel the process of microbialization on reefs. Additionally, there are other examples of reefs that are subjected to high loads of organic and inorganic nutrients as well as pollution, like Vardero reef in Colombia (Pizarro et al, 2017) or reefs subjected to upwelling events (Leichter et al, 2003;Stuhldreier et al, 2015). Comparisons of microbial community dynamics between these drastically different reef regimes like Vardero reef with JR would extend our knowledge of how microbial communities contribute to energy cycling and reef health.…”
Section: Revisiting the Microbialization Hypothesis In The Context Ofmentioning
confidence: 99%
“…However, future studies would benefit from collecting samples at a higher spatial or temporal resolution in order to unravel the process of microbialization on reefs. Additionally, there are other examples of reefs that are subjected to high loads of organic and inorganic nutrients as well as pollution, like Vardero reef in Colombia (Pizarro et al, 2017) or reefs subjected to upwelling events (Leichter et al, 2003;Stuhldreier et al, 2015). Comparisons of microbial community dynamics between these drastically different reef regimes like Vardero reef with JR would extend our knowledge of how microbial communities contribute to energy cycling and reef health.…”
Section: Revisiting the Microbialization Hypothesis In The Context Ofmentioning
confidence: 99%
“…Sub-samples were kept dark and frozen until the end of the study period and were analyzed for nitrate (NO ) and nitrite concentrations using a Thermo Scientific UV Evolution 201 ® photometer based on a method revised by García-Robledo, Corzo & Papaspyrou (2014) ( ; LOD (NO x ) = 0.162 µmol L −1 ). A detailed description of the temporal variability in physicochemical and organic parameters at the study site can be found in Stuhldreier et al (2015) .…”
Section: Methodsmentioning
confidence: 99%
“…However, future studies would benefit from collecting samples at a higher spatial or temporal resolution in order to unravel the process of microbialization on reefs. Additionally, there are other examples of reefs that are subjected to high loads of organic and inorganic nutrients as well as pollution, like Vardero reef in Colombia (Pizarro et al 2017) or reefs subjected to upwelling events (Leichter et al 2003;Stuhldreier et al 2015). Comparisons of microbial community dynamics between these drastically different reef regimes like Vardero reef with Jardines de la…”
Section: Revisiting the Microbialization Hypothesis In The Context Ofmentioning
confidence: 99%